A new species of ocellated Xanthias Rathbun, 1897 (Crustacea: Decapoda: Brachyura: Xanthidae) from the Bohol Sea, Philippines - Mendoza, Jose Christopher E. (Zootaxa, 2013)
A new species of xanthid crab (Brachyura: Xanthidae) is described from the Bohol Sea in the central Philippines. Xanthias joanneae sp. nov. is most similar in morphology to X. maculatus Sakai, 1961 (type locality: Sagami Bay, Japan), partic-ularly in the presence of distinctive ocelli on the carapace and pereopods. It can be separated from this species by the great-er number of ocelli on the dorsal surface of the carapace, wider teeth separated by narrow notches on the carapace anterolateral margin, absence of longitudinal ridges on the external surface of the chelar palm, shorter and stouter ambu-latory legs, narrower male anterior thoracic sternum, and stouter G1.